Альфа-Е-катенін у гістологічних перебудовах міокарда при старінні - Балацький, В.В.; Акименко, І.; Мацевич, Л.Л.; Півень, О.О.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2016)
Aim. In our current work we have focused on cardiospecific ablation of alpha-E-catenin during cardiogenesis and its
reflection on postnatal heart. Methods. Kaplan-Meier analysis of mutant and WT mice survival. Histological analysis
(hematoxylin-eosin and van Gieson stain) of old transgenic and wild-type animals. The HW/BW and HW/TL index was
calculated to estimate myocardium hypertrophy development. Results. Alpha-E-catenin deletion leads to shorten life span
of mutant mice. We observed increased heart weight, histological abnormalities of myocardium and increased fibrosis
in hearts of mice with alpha-E-catenin deletion. Conclusions. We have shown that embryonic cardiac specific deletion
of such as one as well as both alleles of the alpha-E-catenin gene leads to disorders of the heart structure, which typical
of dilated cardiomyopathy, ischemic heart disease, accompanied by fibrosis. As a result all this violation of heart tissue
structure occur early death of animals. We assume that the loss of alpha-E-catenin leads to such dramatic consequences
not only due to violation of cells interactions, but deregulation of signalling passways in cardiomyocytes, it’s should be
clarified with further molecular genetics and physiological studies.
Keywords: α-catenin, gene deletion, heart, heart development.